Fibonacci 3-Parameter Generalized Quaternions - BİLGİCİ, Göksal (European Journal of Science and Technology, 2022)
There are many studies on Fibonacci quaternions and their generalizations. Recently, Şentürk and Ünal (2022) introduced 3-parameter generalized quaternions. The goal of this study is to introduce Fibonacci and Lucas 3-parameter generalized quaternions and to investigate their properties. After obtaining Binet formulas for these quaternions, generalizations of some well-known identities are presented.